2016
DOI: 10.4238/gmr.15028291
|View full text |Cite
|
Sign up to set email alerts
|

High polymorphism at microsatellite loci in the Chinese donkey

Abstract: ABSTRACT. To reveal the genetic diversity and phylogenetic relationships between Chinese donkey breeds, 415 individuals representing ten breeds were investigated using ten microsatellite markers. The observed number of alleles, mean effective number of alleles (N E ), mean expected heterozygosity (H E ), and polymorphic information content (PIC) of each breed and polymorphic locus were analyzed. The results showed that seven (HTG7, HTG10, AHT4, HTG6, HMS6, HMS3, and HMS7) of ten microsatellite loci were polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
5
5
1
Order By: Relevance
“…These results are comparable to the previous values reported in Balkan donkeys [35], Spanish donkeys [36] and Catalonian donkeys [37]. In terms of mean number of alleles, the genetic variability observed in the 16 Turkish donkey populations was lower than that reported in Catalonian donkey breed [37], five Spanish breeds [36], three Croatian donkey populations [38], 15 indigenous Chinese donkey breeds [39][40][41][42], Balkan donkeys [35] and Tunisian donkeys [43], but higher than that observed in the seven indigenous Italian donkey breeds [44][45][46][47].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…These results are comparable to the previous values reported in Balkan donkeys [35], Spanish donkeys [36] and Catalonian donkeys [37]. In terms of mean number of alleles, the genetic variability observed in the 16 Turkish donkey populations was lower than that reported in Catalonian donkey breed [37], five Spanish breeds [36], three Croatian donkey populations [38], 15 indigenous Chinese donkey breeds [39][40][41][42], Balkan donkeys [35] and Tunisian donkeys [43], but higher than that observed in the seven indigenous Italian donkey breeds [44][45][46][47].…”
Section: Discussionsupporting
confidence: 84%
“…The results of microsatellite polymorphism revealed relatively high degree of heterozygosity in the Turkish donkey populations investigated in this study. Among Turkish donkey populations, the H E ranged from 0.6294 (ISP) to 0.6983 (ANT), which showed a comparable level to the previous values reported in Spanish donkeys [ 36 ], Catalonian donkey breeds [ 37 ], Croatian coast donkey populations [ 48 ], Balkan donkey breeds [ 35 ], Tunisian donkeys [ 43 ], Chinese donkey breeds [ 39 , 40 , 41 , 42 ] and was more diversified than Italian [ 44 , 45 , 46 , 47 ] and American donkeys [ 49 ]. This finding indicates that there are appreciable differences in the level of genetic variability among 16 Turkish donkey populations.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results indicated that the microsatellites of similar species are conserved and could be used to analyze the genetic diversity of donkeys. Researchers also needed to have a deeper understanding of the genetic information and genetic relationships within and among breeds to obtain more accurate and generalized conclusions, which could be more effectively applied to the conservation and further utilization of donkey breeds [ 35 , 36 , 37 ]. In terms of average allele number, the genetic variability observed in three Sicilian donkey breeds should be lower than in five Spanish and three Croatian breeds but higher than in the Italian Amiata donkey [ 38 ].…”
Section: Research On Genetic Materialsmentioning
confidence: 99%